Use of the SSCP technique to detect point mutations on human mtDNA - Estrada-Cuzcano, Alejandro (2005)
We evaluate the use of SSCP (single strand conformational polymorphism), a relatively easy and inexpensive technique for the detection of point mutations with a sensibility around 80% under ideal conditions. To test the technique, we used samples of volunteers whose DNA had been previously characterized for the presence or absence of 5 mitochondrial RFLPs. Optimization of the tests included variations in TBE (1X and 0,5X) and of glycerol concentration (10%, 5% and no glycerol) in polyacrylamide gels. Four out of five RFLPs were detected under the conditions used and could be applied routinely without using restriction enzymes. In addition, the SSCP technique allowed detection of unknown mutations in a 394 bp nucleotide segment of the hypervariable (HVI) region of mtDNA. Differences corresponding to different haplotypes were detected, helping to distinguish groups within the same subtype. Sequencing of two samples of subtype B1 with differential migration on SSCP gels, proved the existence in seven different nucleotides.